Tolerance of Micronized Mineral Pigments for Intrastromal Keratopigmentation: A Histopathology and Immunopathology Experimental Study. Issue 9 (September 2016) - Amesty, Maria A.; Rodriguez, Alejandra E.; Hernández, Enrique; De Miguel, Maria P.; Alio, Jorge L.
Abstract : Purpose: To study the tolerance and biocompatibility of mineral pigments for corneal pigmentation histopathologically and immunologically in an experimental animal model. Methods: Manual intralamellar keratopigmentation was performed in 28 New Zealand white rabbits using micronized mineral pigments. Histopathological examination was performed 3 months after the surgery to determine the level of pigment diffusion, the level of inflammation, and the presence/absence of neovascularization. An immunological analysis was also performed. Results: No pigment diffusion or changes in color, inflammation, or neovascularization were detected in the treated eyes. Histopathological examination corroborated clinical results regarding inflammation. Pigmented corneas showed a good cosmetic appearance without signs of ocular toxicity. From the immunological perspective, the pigments do not generate an inflammatory response in the rabbit cornea or in vitro. Conclusions: Micronized mineral pigments could be a valid alternative treatment for corneal pigmentation. Manual intralamellar keratopigmentation technique presented good cosmetic appearance without adverse effects in the treated eyes.